Case marking in Hungarian children with specific language impairment. Issue 4 (August 2013) - Lukács, Ágnes; Kas, Bence; Leonard, Laurence B.
This study examines whether children with specific language impairment (SLI) acquiring a language with a rich case marking system (Hungarian) have difficulty with case, and, if so, whether the difficulty is comparable for spatial and nonspatial meanings. Data were drawn from narrative samples and from a sentence repetition task. Suffixes were tested both in their spatial and nonspatial meanings. Participants with SLI were compared to same-age peers and younger typically developing children matched on receptive vocabulary scores (VC children). Results show that although case marking errors are very rare in spontaneous speech in Hungarian children with SLI, the number of case-marked nouns and of different case markers is significantly lower in children with SLI. In the elicited production task, overall performance of the children with SLI was significantly below that of VC children, but children with SLI and VC children scored higher with spatial than with nonspatial meanings. The results are in line with expectations based on processing accounts which posit greater difficulties with less transparent details of grammar.